Análise térmica de pilares de concreto armado expostos ao fogo - Almeida, Thamyrys Morgana Pontes de (2018)
The structures exposed a fire scenario undergo transformations characterized by the degradation of the strength and stiffness of the constituent materials and by the deformations introduced by the corresponding temperature variation. Although the concrete is a material with good resistance to fire and low thermal conductivity, fire cases show the importance of the study of the behavior reinforced concrete structures subjected to high temperatures. The analysis of the performance of a structural element under the action of temperature requires the knowledge of the evolution of the fields of temperature and of the flow of heat in its interior. As a function of the temperature distribution within the structural element at each instant, an evaluation of its current strength and stiffness can be made, degraded by the effects resulting from the thermal action. The present work aims to show a simplified methodology that allows the evaluation of the temperature distribution in reinforced concrete columns submitted to high temperatures. Rectangular section columns central and inserted in masonry wall are analyzed, in addition to the efficiency of an outer layer of fire protection coating. In the case of central columns, the external thermal action is assumed to be spatially symmetrical and, for the columns inserted in masonry, it is assumed that the external flow is unidirectional, incident laterally on one of the faces. The analysis are performed through a transient thermal model developed based on the finite difference method using the Matlab software and the results are presented in the form of curves and mappings that illustrate the evolution of the temperature inside the cross sections as a function of time.